Improving students’ motoric skills through demonstration method in recycling plastic waste - Ilmi Zajuli Ichsan; Surandini Wahyu Widi Mulyani (University of Muhammadiyah Malang, 2018)
One of the obstacles faced in school is the low motoric skills of students in recycling waste meanwhile the motoric skills are one of the learning outcomes that must be developed. The purpose of this research was to improve students' motoric skills in recycling plastic waste. This Classroom Action Research was conducted in three cycles. The subjects in this research were 34 students of 7th grade. The data was collected by using observation method in which the skill indicators instrument utilized was adopted from Arikunto. The research was conducted in March 2018. The results showed that there was an increasing trend of students’ motoric skills in each cycle. On the other words, the demonstration method can improve students’ motoric skills in recycling plastic waste.